Assessment of Success of Restoration after Chemo Mechanical Caries Removal by Using Papain Based Gel - Asma Rashid, Wajahat Hussain, Hira Asghar, Mamoona Shah, Sajida Gul, Fatima Khalid Qazi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the restoration’s success after chemo mechanical caries removal by using papain based gel. Study Design: Descriptive case study Place and Duration of Study: This study was conducted at the Operative Dentistry Department from March, 2019 to August, 2021. Methodology: Two hundred patients were selected. All Patients of both genders having age of 8-16 years were included and patients with presence of fistula and patients having history of pain were excluded. Papain based gel had been applied to the cavity and allows 40-50 seconds for the gel to work, and the patients had been followed up for 30 days for evaluation of restoration. Results: The average age was 14.07±1.88 years. The success of restoration was present in 82.0% while it was absent in 18.0%. Conclusion: Removal of caries after chemo mechanical by using papain based gel showed high efficacy of success of restoration.